Wheat Development and Yield as Affected by Era of Variety Release and In-Furrow Fertilizer - R. E. Maeoka; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2018)
Nutrients play a major role in wheat yield determination; however, limited information exists on the differential responses of historical and modern varieties to in-furrow fertilizer. Our objectives were to estimate grain yield and differences in agronomic traits of historical and modern winter wheat varieties as affected by different fertilization programs. Two field trials were established during the growing season 2016–2017 (i.e., Ashland Bottoms and Belleville, KS). Seven winter wheat varieties released between 1920 and 2016–Kharkof (1920), Scout 66 (1966), Karl 92 (1988), Jagalene (2001), Fuller (2006), KanMark (2014), and Larry (2016)–were sown using one of two different fertilizer practices: either the university recommendation or a treatment where 100 lb/a MESZ were applied in-furrow. At both locations, historical varieties were taller and had thinner stems than modern ones. In-furrow fertilizer increased yield of modern varieties relative to no fertilizer treatment in a sandier soil in Ashland Bottoms, while historical varieties showed neutral to negative yield response. In the silt loam soil near Belleville, there was only a significant variety effect but no fertilizer effect, likely due to a greater cation exchange capacity of the studied soil. More site-years of this study are needed to determine whether there is a need for re-evaluation of current fertility recommendations for modern wheat varieties.
Keywords: Wheat; historical varieties; modern varieties; in-furrow fertilizer